Some acute phase proteins, oxidative stress biomarkers and antioxidant enzyme activities in ewes with pregnancy toxemia - Gurdogan, F.; Balikci, E.; Yildiz, A. (Shiraz Univ, 2014)
The aim of this study is to investigate antioxidant enzymes, oxidative stress biomarkers and the acute phase proteins levels for subclinical and clinical pregnancy toxemia and to determine the effect of early diagnosis on the success of curing. According to the results of clinical and biochemical parameters, from 39 ewes, 10 were healthy ewes (control group), 13 ewes had subclinical pregnancy toxemia (subclinic group) and 16 had clinical pregnancy toxemia (clinic group). Glucose level and glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase (CAT) activity in clinic group were found statistically lower than in the other groups (P<0.05); as for BHBA, cortisol, MDA, SAA and Hp were found higher than in the other groups (P<0.05). In subclinic group BHBA, SAA and Hp were statistically higher than in control group (P<0.05). Conclusively, the parameters of oxidative stress, antioxidant enzymes activity and acute phase proteins (AAPs) can be used for the diagnosis of pregnancy toxemia in pregnant ewes.
Keywords: Pregnancy toxemia; Acute phase protein; Oxidative stress; Antioxidant; Ewe